Causes and predictors of death among Finnish patients with systemic sclerosis - Kortelainen, Saara (Informa Healthcare, 2025)
Objective: The aim of this study was to assess causes and predictors of death among Finnish patients with systemic sclerosis (SSc).
Method: Medical records of patients registered with the ICD-10 code M34 from 1996 to 2018 in two university hospitals were reviewed retrospectively. Clinical data were collected until the end of 2020. Death certificates were obtained from Statistics Finland up to August 2021. Using death certificates and patient records, the cause of death for each patient was determined. The mean age at death, median time from SSc diagnosis, and factors predicting death were analysed.
Results: Among 313 SSc patients, 91 deaths occurred between April 2000 and September 2020. Overall 5 and 10 year survival rates were 88.4% and 80.2%, respectively. SSc was the most common primary cause of death (n = 35) and interstitial lung disease (ILD) was the most common SSc-related cause of death (n = 13). Moreover, 52% of the patients with diffuse SSc and 33% of those with limited cutaneous SSc died as a result of SSc itself. Patients who died because of SSc were significantly younger [mean ± sd age 65.6 ± 12.7 years, 95% confidence interval (CI) 61.2-70.1] than those who died from other causes (74.2 ± 9.6 years, 95% CI 71.5-76.9) (p = 0.0006). ILD, pulmonary arterial hypertension, gastrointestinal involvement, male gender, and older age at disease onset predicted death.
Conclusion: The disease itself was the major cause of death among Finnish SSc patients, in both diffuse and limited forms of SSc.